2022
DOI: 10.1021/acs.analchem.2c02096
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous Detection of Three Genotypes of Gene Methylene Tetrahydrofolate Reductase and Methionine Synthase Reductase Based on Multiplex Asymmetric Real-Time PCR-HRM Biosensing

Abstract: Genotyping of folate metabolism genes is of great importance in disease diagnosis and prevention. However, most current detection methods used for folate metabolism gene genotyping are based on sequencing and chips, which suffer from a high cost and laborious and time-consuming procedures. Herein, we reported a multiplex asymmetric PCR-HRM strategy for identifying genotypes of folate metabolism genes in a single tube. The proposed multiplex PCR-HRM assay has been successfully applied to identify the genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…SNP detection techniques that employ real-time PCR with closed tube systems are currently the most prevalent methods used in clinical practice. Among these techniques, TaqMan probe- 3 and dual-labeled probe-mediated high-resolution melt curve methods 4 are the most commonly utilized. In addition, most commercially available SNP genotyping kits, authorized by China National Medical Products Administration (NMPA), US Food and Drug Administration (FDA), and European Conformity (CE) marking, are based on these techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SNP detection techniques that employ real-time PCR with closed tube systems are currently the most prevalent methods used in clinical practice. Among these techniques, TaqMan probe- 3 and dual-labeled probe-mediated high-resolution melt curve methods 4 are the most commonly utilized. In addition, most commercially available SNP genotyping kits, authorized by China National Medical Products Administration (NMPA), US Food and Drug Administration (FDA), and European Conformity (CE) marking, are based on these techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multiplex asymmetric PCR based detection has evolved a rapid and convenient tool in wide variety of bioanalyses ( Zhu et al, 2007 ; Yu et al, 2022 ; Kong et al, 2023 ). It uses many pairs of unequal concentrations of the primers for amplification, generating single stranded amplicons.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates the simultaneous amplification of many targets of interest in one reaction, thus enhancing assay throughput and allowing more efficient use of each sample. Previous study has reported the development of multiplex polymorphism detection in a single tube for screening folate metabolism genes ( Yu et al, 2022 ). Additionally, it has been utilized to identify seven immune-escape RBD mutations of Omicron ( Kong et al, 2023 ), as well as detecting drug resistance genes in Enterobacteriaceae ( Zhu et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%